Carbon isotopic ratio of lipid fraction to trace fractionation processes in cull cows organism and to discriminate between different feeding regimes. (December 2021) - Pianezze, Silvia; Corazzin, Mirco; Perini, Matteo; Sepulcri, Angela; Saccà, Elena; Piasentier, Edi
Abstract: In the present work, the quantification of the lipids and the carbon isotopic ratio (δ 13 C) of diet, rumen, liver and meat lipids of cows fed on different diets (based on either C3 or C4 plants) are provided. The δ 13 C of the four compartments had different trends in the two diets, which could give information about the fractionation processes and the factors influencing the lipids metabolic path in cows fed on different regimes. The δ 13 C of liver and meat lipids resulted to be statistically different for cows of groups C3 and C4, and can therefore be a suitable tool to discriminate between the two groups.